If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
0*(1/5)-((1/2)*y) = 1 // - 1
0*(1/5)-((1/2)*y)-1 = 0
(-1/2)*y-1 = 0
-1/2*y-1 = 0 // + 1
-1/2*y = 1 // : -1/2
y = 1/(-1/2)
y = -2
y = -2
| 60y-20(0)=-120 | | 60(0)-20x=-120 | | (u+7)x(u-4)= | | (5y/7)-(6/7)=2-4y | | 3x+3y=5x-5y | | (0)-2y=8 | | D=70m | | 5x=(342/9) | | -2(0)+3y=-6 | | -2x+3(0)=-6 | | 3x=(76/5) | | 2x=(76/5) | | 9w=6660 | | lnx=2+ln(1-x) | | D=8cm | | 2x=(76/4) | | 2x-5=x(3-7)+12 | | x-b/a=6 | | log(x^2+6)-log(x-1)=1 | | log*2(2x-4)=2+log*2(x^2-6) | | X^2-4/5X0 | | 147-3x=90 | | 5x+5=-7-6x | | -10(-4+2)=2(-2y) | | -7(x-1)=5x+3 | | 407+40=-50y-50 | | -15+2p=p+20 | | 10-k=4k-14 | | 5y=-3x-6 | | 4a+44-6=a | | y-4=5y+8 | | 7(s+1)=-3 |